2008 Proceedings IEEE INFOCOM - The 27th Conference on Computer Communications 2008
DOI: 10.1109/infocom.2007.175
|View full text |Cite
|
Sign up to set email alerts
|

Realistic and Efficient Multi-Channel Communications in Wireless Sensor Networks

Abstract: Abstract-This paper demonstrates how to use multiple channels to improve communication performance in Wireless Sensor Networks (WSNs). We first investigate multi-channel realities in WSNs through intensive empirical experiments with Micaz motes. Our study shows that current multi-channel protocols are not suitable for WSNs, because of the small number of available channels and unavoidable time errors found in real networks. With these observations, we propose a novel tree-based multichannel scheme for data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 5 publications
1
76
0
Order By: Relevance
“…Previous work [6] has reported that adjacent overlapping channels have undesired inter-channel interferences. In this section, we first investigate the impacts of overlapping channels on packet reception ratio (PRR) of link to motivate our work.…”
Section: Empirical Modeling Of Overlapping Channelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work [6] has reported that adjacent overlapping channels have undesired inter-channel interferences. In this section, we first investigate the impacts of overlapping channels on packet reception ratio (PRR) of link to motivate our work.…”
Section: Empirical Modeling Of Overlapping Channelsmentioning
confidence: 99%
“…However, no detailed study has been performed to utilize overlapping channels in wireless sensor networks for improved real-time performance. A coarse-grained channel assignment policy for WSNs is proposed in [6], which allocates nonoverlapping channels to disjoint trees and exploits parallel transmissions among trees. In this paper, we propose to utilize overlapping channels to configure power and channels for a WSN to achieve better real-time performance and energy efficiency.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Tree-based Multi-Channel Protocol (TMCP) [2] supports data collection traffic by partitioning the network into multiple subtrees and then assigns different channels to different subtrees. Hence, inter-tree interference is minimized without the need for time synchronization.…”
Section: Motivationmentioning
confidence: 99%